P775 Usefulness of endoscopic balloon dilation for colorectal strictures in patients with Crohn's disease who underwent administration of TNF-α inhibitor. (16th January 2018) - Takeda, T; Hirai, F; Ishikawa, S; Yano, Y; Masahiro, K; Takada, Y; Beppu, T; Yao, K; Matsui, T; Ueki, T
Abstract: Background: Endoscopic balloon dilation (EBD) has been established as a therapeutic option for Crohn's strictures. This study aimed to clarify the usefulness of EBD for Crohn's disease (CD) patients with receiving TNF-alfa inhibitor. Methods: The subjects were CD patients who received TNF-alfa inhibitor at our hospital. EBD was indicated for patients who had symptomatic benign colorectal strictures without fistula and abscess. The short-term success rate of EBD, the rate of re-dilation, long- term surgery-free rate and adverse events of EBD were investigated retrospectively. The short-term success was defined as disappearance of stenotic symptoms after technically successful EBD. Results: Five hundred and eighty-one CD patients received TNF-alfa inhibitor therapy at least once from January 2005 to September 2017. Of these 581 patients, 49 patients (8%) had experienced EBD for colorectal strictures. The short-term success rate of EBD was 90% (44/49). Although 28 patients (55%) were needed for re-dilation, only 2 patients in the successful EBD group required surgery. Surgery-free rate was significantly higher in the successful EBD group than in unsuccessful group (95% vs. 40%, p < 0.01). Neither severe bleeding that required transfusion nor perforation occurred. Conclusions: EBD for colorectal strictures is useful and safe treatment for CD patients who underwent administration of TNF-α inhibitor.